Monetary policy and fears of financial instability - Vincent Brousseau; Carsten Detken (European Central Bank (ECB), 2001)
Exploiting a specific sunspot equilibrium in a standard forward-looking New Keynesian model, we present an example of a possible conflict between short-term price stability and financial stability. We find a conflict because the sunspot process consists of a self-fulfilling belief linking the stability of inflation to the smoothness of the interest rate path. A policy focusing only on a fixed-horizon inflation forecast neglects the potential effects of this belief on the variance of inflation. The nature of the conflict case is interpreted as evidence for the occasional relevance as well as the general tenuousness of the conflict case. The implementation of our example has led us, furthermore, to illustrate the lack of general applicability of the Bellman principle in dynamic programming for forward-looking models. Our result holds with respect to a more general (Nash-type) concept of optimality
Keywords: C61; C62; E52; E58; 330